Обґрунтування умов підвищення продуктивності, точності та якості обробки при алмазному шліфуванні - Дитиненко, Станіслав Олександрович; Крюк, Анатолій Григорович; Новіков, Федір Васильович (НТУ "ХПІ", 2018)
Розроблено математичні моделі визначення продуктивності обробки, пружних переміщень, що виникають в технологічній системі, та шорсткості поверхні при круглому зовнішньому поздовжньому шліфуванні алмазними кругами на металевих зв'язках твердосплавних виробів. Показано, що домогтися істотного зменшення шорсткості поверхні при шліфуванні можна створенням на алмазному крузі плосковершинних зерен. Це дозволяє виключити з технологічного процесу операцію притирання алмазними пастами і скоротити час обробки. На цій основі розроблено і впроваджено у виробництво ефективну технологію шліфування алмазними кругами на металевих зв'язках з плосковершинними зернами твердосплавних виробів, що забезпечує високі показники продуктивності обробки, точності та шорсткості оброблених поверхонь.

Mathematical models have been developed for determining the productivity of processing, the elastic displacements arising in the technological system, and the surface roughness during round external longitudinal grinding with diamond circles on metal sheaves of hard-alloy products. The classification of various grinding patterns by the periphery of the circle was made according to the kinematic feature of the time of formation of the established surface roughness, taking into account the influence of the different height of grains, the probabilistic nature of their participati on in cutting and the presence of areas on the tops of the grains. It is shown that a significant reduction in surface roughness during grinding can be achieved by creating flat-topped grains on the diamond wheel. This allows you to exclude the operation of grinding with diamond pastes from the process and reduce processing time. On this basis, an effective technology of grinding with diamond circles on metal bundles with flat-topped grains of carbide products, which provides high rates of processing performance, accuracy and roughness of the processed surfaces, has been developed and introduced into production.
Justification of conditions for increasing productivity, accuracy and quality of processing during diamond grinding
Keywords: технологічний процес; алмазний круг; шорсткість поверхні; пружні переміщення; технологічна собівартість обробки